Competências do enfermeiro para atuação na atenção domiciliar e situações que mobilizam as competências: estudo de caso - Roseli Lino de Souza (2023)
Introduction: Home health care is an expanding modality of care on the world stage and the nurse is part of the multidisciplinary team, being the largest provider of home care. In the context of specificities of home care, nurses are constantly challenged to mobilize knowledge, skills and attitudes in an interrelated way and are expected to be competent in professional practice. The objective of this study was to analyze the skills mobilized by nurses in home care in their day-to-day work. Method: qualitative approach study with a single case study methodological design. Data production took place in home care service of the Unified Health System in the city of Belo Horizonte. 12 nurses who make up multidisciplinary home care teams participated in the research. The sources of evidence were documents analysis, interviews guided by a semi-structured script focusing on skills and focus groups. The data were submitted to Critical Discourse Analysis, from Fairclough 's perspective, enabling the discussion of two empirical categories: nurse skills to work in home care; and situations that promotes the mobilization of skills. Results: a set of seventeen skills mobilized by nurses in home care service were identified, namely: leadership, communication, decision making, holistic assessment of the patient and home environment, work management, care management, health education, cultural sensitivity, nursing care, teamwork, interdisciplinary collaboration, networking, material resource management, time management, professional development, adaptation to technology and work safety. For each of the competencies, attributes related to knowledge, skills and attitudes were highlighted and discussed. The speeches revealed that skills are mobilized by situations related to the particularities of home care, the uniqueness of the home context and professional demands. Conclusion: the practice of nurses in home care mobilizes several skills understood as a necessity in day-to-day work.